A Hypereosinophilic Syndrome Presenting as Eosinophilic Colitis - Jeon, Young Woo (The Korean Society of Gastrointestinal Endoscopy, 2012)
Hypereosinophilic syndrome (HES) has three defining features: marked hypereosinophilia for at least 6 months, no confirmed etiology for the eosinophilia, and eosinophilia-related symptoms or organ dysfunction. However, a shorter period of hypereosinophilia with symptoms requiring eosinophil-lowering therapy is also acceptable. We report a case of HES presenting as eosinophilic colitis. Although hypereosinophilia was present for 3 months, this patient needed to be treated with eosionphil-lowering therapy for severe hematochezia. After systemic corticosteroid therapy, symptoms caused by organ involvement were dramatically improved.